2021
DOI: 10.3390/microorganisms9112297
|View full text |Cite
|
Sign up to set email alerts
|

In Silico/In Vitro Strategies Leading to the Discovery of New Nonribosomal Peptide and Polyketide Antibiotics Active against Human Pathogens

Abstract: Antibiotics are majorly important molecules for human health. Following the golden age of antibiotic discovery, a period of decline ensued, characterised by the rediscovery of the same molecules. At the same time, new culture techniques and high-throughput sequencing enabled the discovery of new microorganisms that represent a potential source of interesting new antimicrobial substances to explore. The aim of this review is to present recently discovered nonribosomal peptide (NRP) and polyketide (PK) molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 94 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…Molecular studies identified multi-domain enzymes responsible for natural product production with antimicrobial activities. These studies investigated the presence and diversity of antimicrobial biosynthetic polyketide synthase (PKS) and non-ribosomal peptide synthetase (NRPS) genes, and their clusters within the cave microbiome [47]. The presence of these enzymes was detected in the caves' microbiome of Belgium [48], India [11,49], Bahamas [50], and Georgia [51].…”
Section: Antagonism Against Phytopathogensmentioning
confidence: 99%
“…Molecular studies identified multi-domain enzymes responsible for natural product production with antimicrobial activities. These studies investigated the presence and diversity of antimicrobial biosynthetic polyketide synthase (PKS) and non-ribosomal peptide synthetase (NRPS) genes, and their clusters within the cave microbiome [47]. The presence of these enzymes was detected in the caves' microbiome of Belgium [48], India [11,49], Bahamas [50], and Georgia [51].…”
Section: Antagonism Against Phytopathogensmentioning
confidence: 99%
“…Especially in recent years, the research on bioactive peptides has gradually become active, and the prospects are becoming more and more promising. The current research and development directions of BAPs are roughly as follows: (1) The discovery of new active peptides, structural analysis, and activity research, and so forth 19 ; (2) Development of targeted enzymatic hydrolysis technology for protein preparation of active peptides, including high‐efficiency and specific enzyme‐producing strains breeding, research on the joint action mechanism of complex enzyme systems, improvement of enzymatic hydrolysis technology, and so forth 20 ; (3) Separation of functional peptides and development of analytical techniques, especially high‐sensitivity, simple, and easy target peptide activity analysis and detection systems and analytical techniques 21 ; (4) Research on functional biological evaluation of peptides 22 ; (5) Development of bioactive peptide medicines and functional foods 23 ; (6) Engineering research on low‐cost, high‐purity, and mass production of bioactive peptides 24 ; (7) Application research of bioengineering technology in the preparation of active peptides, such as protein engineering, 25 enzyme engineering, 26 genetic engineering, 27 cell culture technology, 28 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in recent years, the research on bioactive peptides has gradually become active, and the prospects are becoming more and more promising. The current research and development directions of BAPs are roughly as follows: (1) The discovery of new active peptides, structural analysis, and activity research, and so forth 19 ; (2) Development of targeted enzymatic hydrolysis technology for protein preparation of active peptides, including high-efficiency and specific enzyme-producing strains breeding, research on the joint action mechanism of complex enzyme systems, improvement of enzymatic hydrolysis technology, and so forth 20 ;…”
mentioning
confidence: 99%
“…Scrutiny of the structures of marketed drugs, we found that both polyketides [ 8 ] and indole alkaloids are among the privileged scaffolds [ 9 ]. Polyketides represent a viable source of chemically diverse and biologically active natural compounds, of which many have become important clinical therapeutics [ 10 ].…”
Section: Introductionmentioning
confidence: 99%